IMPLEMENTASI METODE BACKPROPAGATION UNTUK MEMPREDIKSI PEMAKAIAN OBAT DI PUSKESMAS OESAPA - Rowin Djuli; Arfan Y Mauko; Meiton Boru (J-Icon : Jurnal Komputer dan Informatika, 2018)
The medicine management incommunity health clinic is one of important aspect, because the health community clinic will have negative impact in costs if there is inefficiency in managing the medicine, the most used medicine will be out of stock before the re-order due date. In artificial neural network backpropagation method is classified as algorithm learning or traning tend to supervised and using rules of quality correction. Backpropagation is using error output to change the value of qualities in two ways, in backward and forward propagation. In this research, writer applying backpropagation method to predicting the medicine usage in oesapa community health clinic. The data was taken from usage report and medicine order receipt in 2014-2016. Where at 2014-2015 was data training and 2016 was data test. Which is the result of data training has ±99% accuracy and the data test has 70,66% accuracy.